Figure of an Apsara on a pillar in the Mahamandapa - Temples of India Project Team (Jio Institute, 2024)
The square portion of the shaft of the pillar in the mahamandapa (pillared hall) is carved with a niche on each of its four faces. Within these niches are figure sculptures depicting various scenes: some portray apsaras (celestial damsels) engaged in activities such as playing musical instruments, dancing, or playing with a ball. Others depict yogis (ascetics) or royal figures engaged in acts of veneration. One niche notably showcases a sculpture of a four-armed Bhairav.